Microclimatic Effects of Green Spaces and Urban Quality of Life Resilience in Ghanaian Cities - , Christian Kofi Sarpong, Irene-Nora Dinye, Rawuf Awudu, Christopher Kanpiim (Archives of Current Research International, 2025)
The phenomenon of rapid urbanization in Ghanaian cities, Accra and Kumasi, has had negative impacts on heightened environmental stressors, such as temperatures, poor air quality, and a decline in public health. In this context, urban green spaces perform essential ecological and social functions that are being progressively acknowledged in international urban planning practice. This study systematically reviews existing literature to synthesize the effects of green spaces on urban microclimates and residents' quality of life with particular reference to Ghana. Using a systematic search of five academic databases, the review collates empirical and theoretical research from 1984 to 2025. Some limitations were realized. Most notably, there was the risk of publication bias as a result of the restriction of grey literature and non-English sources. Secondly, even though there is increased interest in urban environmental planning in Ghana, empirical studies specific to Ghana remain scarce. The findings are that green infrastructure significantly reduces ambient temperatures, improves humidity balance, air quality, and affects wind circulation, and reduces the urban heat island effect. Green infrastructure also benefits physical and mental health, social cohesion, and civic engagement. Disparities in access, particularly among low-income and marginalized populations, represent a significant barrier to achieving equitable urban development. The study highlights the necessity of integrating green spaces into Ghana's urban planning policies as a strategy for enhancing climate resilience, public health, and environmental justice. The policy priorities demand the foregrounding of native vegetation, equitable access, and mainstreaming of green infrastructure into broader sustainability agendas.